Pro EDI in BizTalk Server 2006 R2 Electronic Document Interchange Solutions - Beckner, Mark (Apress : Imprint: Apress, 2007)
Electronic document interchange, or EDI, is one of the next big waves in connected systems, as business becomes more dependent on working with partners, suppliers, and other organizations in a streamlined way. Microsoft BizTalk Server 2006 R2 offers an efficient, integrated way to deploy EDI solutions, and with Pro EDI in BizTalk Server 2006 R2: Electronic Document Interchange Solutions, you'll see how EDI can be used in your business and how best to get it set up with BizTalk. With a cursory read of this book, management-level resources will be able to quickly determine the complexity of a BizTalk EDI implementation and the level of resources that will need to be made available. The developer will get an in-depth understanding of EDI and a detailed step-by-step approach to building and deploying projects. This book's unique approach sees an EDI project from end to end, through inception, into development, and finally through deployment. With this practical guide, you can set up and deliver a BizTalk 2006-driven EDI solution without getting caught up in the complexity of non-EDI items in BizTalk.